2022
DOI: 10.15406/jabb.2022.09.00282
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus thuringiensis (Bt) is more than a special agent for biological control of pests

Abstract: Bacillus thuringiensis (Bt) is a bacterial genus known mainly for its capability to synthesize, in addition to spores, a parasporal body or crystal (δ––endotoxin), comprised of proteins which are toxic to pest insects, i.e., Coleoptera, Diptera and Lepidoptera, and other orders. As well as plant pathogenic nematode and many other applications as endophytic plant growth promoting bacteria, or cleaning enviornmental form some chemicals polluting agents, and even in human medicine for cancer prevention. The Bt co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 107 publications
0
3
0
Order By: Relevance
“…For the last two decades, the pyrethroid insecticides have usually been exhibited in the proposed and marketed synthetic insecticides mixtures [21][22][23][24][25]. Although Bt-based biopesticides have proven that they have the potential to act as alternative or complementary eco-friendly insecticides on about 3000 insect species, they still need enhancers or synergistic agents to beat the resistant strains of tomato leafminer [29,30]. The integration of biorational insecticides with chemicals is imperative for the successful control of this insect and for the sustainable protection of the environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the last two decades, the pyrethroid insecticides have usually been exhibited in the proposed and marketed synthetic insecticides mixtures [21][22][23][24][25]. Although Bt-based biopesticides have proven that they have the potential to act as alternative or complementary eco-friendly insecticides on about 3000 insect species, they still need enhancers or synergistic agents to beat the resistant strains of tomato leafminer [29,30]. The integration of biorational insecticides with chemicals is imperative for the successful control of this insect and for the sustainable protection of the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Biopesticides based on Bacillus thuringiensis (Bt) have proved their potential for decades as alternative or complementary eco-friendly insecticides on Lepidopteran, Dipteran, Orthopteran, and Coleopteran insects [26][27][28][29]. The Bt-products are environmentally safe for humans, beneficial vertebrates, and arthropods in addition to having no pre-harvest intervals on agricultural products [30,31]. In general, B. thuringiensis is a spore-forming bacteria known for its capability for synthesizing different types of toxic substances such as crystal protein (δ-endotoxin), vegetative insecticidal protein (Vip), and secreted insecticidal protein (Sip) [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Hussein et al (2020) found that the mortality percentage of the mite Oligonychus afrasiaticus (McGregor) varied between 73.3 % and 92 %, after seven days of treatment with B. bassiana, Metarhizium acridum, Lecanicillium muscarium and Isaria fumosorosea. Among bacteria, Bacillus thuringiensis Berliner has been shown to be effective against some mite pests (Erban et al, 2009;Alahyane et al, 2019;Sánchez-Yáñez et al, 2022) against pest insects of the orders coleoptera, diptera, hymenoptera, homoptera, orthoptera, and others (Fang et al, 2009;Ferreira-Agüero et al, 2020;Sánchez-Yáñez et al, 2022). These findings allow us to infer that the pathogenic or endotoxic effects of entomopathogens would prove to be effective against the red spider of the avocado O. yothersi.…”
Section: Introductionmentioning
confidence: 96%